AN ANALYSIS OF EXPENSES STRUCTURE OF HIGHER EDUCATION SCHOOLS IN 2004-2009 - Małys, Anna Ćwiakała (Anales Universitatis Apulensis Series Jurisprudentia; No 16 (2013): ANNALES UNIVERSITATIS APULENSIS - SERIES JURIPRDENTIA, 2013)
In 2004-2009 the costs of universities activity were systematically growing. Didactical activity was generating the highest costs. These costs exceeded the incomes and non-public universities  showed surpluses of income. Public universities showed slight surplus of income over costs of research activity. Whereas, as we consider non-public universities, their costs of research activity significantly exceeded incomes from this activity. Universities had a rigid costs structure. Remunerations constituted the highest share in costs. Key words Public universities, non-public universities, budget expenses, tangible asset-related and financial plan, unit education cost